Polarization constraints on the X-ray corona in Seyfert Galaxies: MCG-05-23-16. Issue 4 (29th September 2022) - Marinucci, A; Muleri, F; Dovciak, M; Bianchi, S; Marin, F; Matt, G; Ursini, F; Middei, R; Marshall, H L; Baldini, L; Barnouin, T; Rodriguez, N Cavero; et al.
ABSTRACT: We report on the first observation of a radio-quiet active galactic nucleus (AGN) in polarized X-rays: the Seyfert 1.9 galaxy MCG-05-23-16. This source was pointed at with the Imaging X-ray Polarimetry Explorer ( IXPE ) starting on 2022 May 14 for a net observing time of 486 ks, simultaneously with XMM- Newton (58 ks) and NuSTAR (83 ks). A polarization degree Π smaller than 4.7 per cent (at the 99 per cent confidence level) is derived in the 2–8 keV energy range, where emission is dominated by the primary component ascribed to the hot corona. The broad-band spectrum, inferred from a simultaneous fit to the IXPE, NuSTAR, and XMM- Newton data, is well reproduced by a power law with photon index Γ = 1.85 ± 0.01 and a high-energy cutoff E C  = 120 ± 15 keV. A comparison with Monte Carlo simulations shows that a lamp-post and a conical geometry of the corona are consistent with the observed upper limit, a slab geometry is allowed only if the inclination angle of the system is less than 50°.